2010
DOI: 10.1007/s10722-009-9511-6
|View full text |Cite
|
Sign up to set email alerts
|

New data on three molecular markers from different cellular genomes in Mediterranean accessions reveal new insights into phylogeography of Pisum sativum L. subsp. elatius (Bieb.) Schmalh.

Abstract: Twelve accessions classified as Pisum sativum subsp. elatius, mostly from West and Central Mediterranean, were analysed for three markers from different cellular genomes: rbcL (plastid genome), coxI (mitochondrial genome) and SCA (nuclear genome). Based on geographical distribution of their allele combinations analysed in this and the earlier study, we suggest a putative history of wild representatives of P. sativum. The ancestor of this species belonged to lineage A (coxI?, rbcL?, SCA f ); it appeared in East… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
53
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(62 citation statements)
references
References 5 publications
8
53
0
1
Order By: Relevance
“…A phylogenetic analysis based on the combination of mitochondrial, chloroplast and nuclear genome markers placed the P. sativum accessions in a distinct clade separated from all P. fulvum and P. sativum subsp. abyssinicum accessions (Kosterin and Bogdanova, 2008;Kosterin et al, 2010) and suggested that all wild forms of Pisum sativum should be included in a paraphyletic P. sativum subsp.…”
Section: Genus Pisum Lmentioning
confidence: 99%
“…A phylogenetic analysis based on the combination of mitochondrial, chloroplast and nuclear genome markers placed the P. sativum accessions in a distinct clade separated from all P. fulvum and P. sativum subsp. abyssinicum accessions (Kosterin and Bogdanova, 2008;Kosterin et al, 2010) and suggested that all wild forms of Pisum sativum should be included in a paraphyletic P. sativum subsp.…”
Section: Genus Pisum Lmentioning
confidence: 99%
“…Он был описан (Braun, 1841) в ранге вида и при нимался многими авторами в этом же ранге (Говоров, 1937;Ellis et al, 1998;Maxted, Ambrose, 2001;Vershinin et al, 2003;Kosterin, Bogdanova, 2008Maxted, Kell, 2009;Jing et al, 2010;Kosterin et al, 2010;Zaytseva et al, 2012Zaytseva et al, , 2015, тогда как иные авторы считают его подвидом посевного гороха P. sativum subsp. abyssinicum (A.…”
Section: таксономический статус абиссинского горохаunclassified
“…Kosterin et al (2010) pointed to the lineage B of P. sativum subsp. elatius as the origin of the cultivated P. sativum while linage A remained as the wild form of the specie.…”
Section: Pumilio)mentioning
confidence: 99%